Հայոց եկեղեցու դերի ընկալումը Հնչակյանների քաղաքական հայեցակարգում (XIX դ. վերջ – XX դ. սկիզբ) - Մկրտչյան, Արամազդ (ՀՀ ԳԱԱ Պատմության ինստիտուտ)
In this article, based on a variety of sources and research, an attempt was made to introduce the idea of Hnchakyan, party relating to the Armenian Church and the assessment of the role of the Armenian clergy, and availability to their proposed solutions. В данной статье, на основе различных источников и научных исследований, сделана попытка представить идеи Гнчакянов, которые связаны с армянской церковью и оценкой роли армянского духовенства.
Keywords: Հայոց պատմություն; Քաղաքական կուսակցություններ; Կրոն; Հասարակական-քաղաքական կյանք